Spatial Differentiation In Industrial Dynamics: A Core-Periphery Analysis Based On The Pavitt-Miozzo-Soete Taxonomy - M. Capasso; Elena Cefis; K. Frenken (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2010)
We compare the industrial dynamics in the core, semi-periphery and periphery in The Netherlands in terms of firm entry-exit, size, growth and sectoral location patterns. The contribution of our work is to provide the first comprehensive study on spatial differentiation in industrial dynamics for all firm sizes and all sectors, including services. We find that at the aggregate level the spatial pattern of industrial dynamics is consistent with the spatial product lifecycle thesis: entry and exit rates are highest in the core and lowest in the periphery, while the share of persistently growing firms is higher in the periphery than in the core. Disaggregating the analysis to the sectoral level following the Pavitt-Miozzo-Soete taxonomy, findings are less robust. Finally, sectoral location patterns are largely consistent with the spatial product lifecycle model: Fordist sectors are over-represented in the periphery, while sectors associated with the ICT paradigm are over-represented in the core, with the notable exception of science-based manufacturing.
Keywords: 330; Entry; exit; spatial product lifecycle; Fordist paradigm; ICT paradigm